Water quality, abalone growth and the potential for integrated mariculture on a South African abalone Haliotis midae L. farm - Yearsley, Rowan David (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2008)
Abalone Haliotis midae farming in South Africa is highly intensive, employing pump-ashore, flow-through systems. Despite the known sensitivity of abalone to water quality, there is only a rudimentary understanding of water quality dynamics on South African abalone farms and its effects on abalone production. Furthermore, the potential for reusing the relatively dilute abalone farm effluent to culture other animal species has not been investigated. This study investigated the dynamics of water quality and growth on a South African abalone farm and assessed the suitability of the effluent for the culture of silver kob Argyrosomus inodorus and bloodworm Arenicola loveni loveni. Monitoring of water quality and abalone growth in abalone tanks revealed that oxygen concentrations decreased, while Hâ º ion and free-ammonia (NHâ‚ƒ) concentration increased in a gradient between the inflow and outflow. Abalone growth was positively correlated with oxygen concentration and negatively correlated with free-ammonia and Hâ º ion concentration. The oxygen (O) concentration of the farm influent was dependent upon the influents' temperature (T) and was described by the relationship O (mg Lâ »Â¹) = 11.244 "“ 0.208T (rÂ²=0.74). Linear regression analysis of data collected from abalone farm tanks revealed that the concentration of total ammonia at the outflow of abalone tanks (Î¼g TAN Lâ »Â¹) was dependant upon temperature (Â°C), flow-rate (L sâ »Â¹ kgâ »Â¹ H. midae), abalone size (g) and length of time since the tank was last cleaned (d) (n = 125, rÂ² = 0.80). The production of total ammonia (Î¼g TAN sâ »Â¹ kgâ »Â¹) was related to temperature, abalone size and days that the tanks remained un-cleaned (n = 125; rÂ² = 0.81). A diurnal cycle of respiration was evident in abalone tanks with higher oxygen consumption and H+ ion production at night. The oxygen concentration of farm effluent was related to temperature, farm biomass and flow rate by means of a linear regression equation (n = 40; rÂ² = 0.69). The results demonstrated the importance of optimising the flow-rate per unit of biomass for various temperatures and sizes of abalone. As abalone size and temperature cannot be controlled under farm conditions, the flow-rate per unit of biomass which the abalone culture system receives will determine the quality of the culture water. The specific growth rate (0.48 Â± 0.01 % BW dâ »Â¹), mortality (1.8 Â± 0.5 %), feed conversion ratio (3.0 Â± 0.2) and protein efficiency ratio (1.0 Â± 0.1) of silver kob kept in either abalone farm effluent or control seawater for 120 days did not differ significantly (t-test, P>0.05). A 90 day growth trial indicated that abalone farm effluent is a suitable culture medium for bloodworm. Bloodworm supplied with control seawater lost weight at 0.19 Â± 0.04 % BW d-1, while those given abalone effluent grew at 0.39 Â± 0.07 % BW dâ »Â¹. Mortality was 6 Â± 3 % in effluent and 11 Â± 8 % in seawater. The bloodworm were efficient at processing solid waste. Abalone farm effluent initially contained 7.7 Â± 13 mg Lâ »Â¹ more suspended solids than control seawater, which contained 3.5 Â± 0.5 mg Lâ »Â¹, but after passing through bloodworm systems the concentration in abalone effluent was reduced to only 1.4 Â± 3.5 mg Lâ »Â¹ above that in control seawater. Therefore, abalone farm effluent could be reused as a culture medium for both silver kob and bloodworm. Future work is needed to investigate aspects of the feasibility of such systems such as growth rates at different sizes and stocking densities.
Keywords: Abalones -- South Africa; Abalone culture -- South Africa; Abalones -- Growth; Mariculture -- South Africa; Water quality -- South Africa